Hegel’s Ethical View in the Light of his Criticisms of Kant’s Ethical View - hasan ahmadizade (اخلاق وحیانی)
Immanuel Kant, in his Groundwork of the Metaphysic of Morals, introduced his only aim the search for and the establishment of the highest moral principle, the one which can work as a compass for ethical actions. But, Hegel believed that Kant’s ethical view was abstract and seemed somewhat empty. In addition, Kant’s ethical principles had contradictions that made it practically infeasible. Kant thought of ethics primarily as something belonged to the individual sphere. But, for Hegel, thinking of ethics as an individual matter mean to ignore the social and political world which is hidden behind the ethical actions of the individual. Furthermore, for him, Kant’s insistence on generalizing the ethical law could be subject to some objections. For example, generalizing the rules is only a negative test, that is, even if it passed successfully, it would show only that what we must not do, not what we must do. In this essay, we want to analyze the most important principles of Hegel’s ethics with respect to his criticisms of Kant’s ethical view.